2003
DOI: 10.1016/s0079-6107(03)00024-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute ventricular volume manipulation on in situ cardiomyocyte cell membrane configuration

Abstract: Effects of mechanical stimulation on cardiac electrical activity, gene expression, protein synthesis, and tissue remodelling have received increasing attention in recent years, as reviewed in this issue of PBMB. Little is known, though, about how changes in ventricular filling affect the cell configuration of cardiomyocytes in the ventricular wall. Here, we present first electron-microscopic insight into changes in cardiomyocyte cell structure in situ during acute ventricular volume manipulation. Apart from co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 15 publications
4
55
0
Order By: Relevance
“…Models suggest that ephaptic or field coupling to surrounding passive tissue could be important in propagation of electrical signals through the myocardium, beyond classical cable model representations [90][91][92]. These findings underscore that changes in cell membrane configuration, observed to occur with stretch, could play an important role in mechanosensitivity cardiomyocyte electrophysiology [49,[93][94][95]]. An electrotonic effect of coupling between cardiomyocytes and cardiac fibroblasts has been demonstrated, in experiments and in simulations [96][97][98][99].…”
Section: Cell Scale: Myocyte Electromechanical Couplingmentioning
confidence: 89%
See 1 more Smart Citation
“…Models suggest that ephaptic or field coupling to surrounding passive tissue could be important in propagation of electrical signals through the myocardium, beyond classical cable model representations [90][91][92]. These findings underscore that changes in cell membrane configuration, observed to occur with stretch, could play an important role in mechanosensitivity cardiomyocyte electrophysiology [49,[93][94][95]]. An electrotonic effect of coupling between cardiomyocytes and cardiac fibroblasts has been demonstrated, in experiments and in simulations [96][97][98][99].…”
Section: Cell Scale: Myocyte Electromechanical Couplingmentioning
confidence: 89%
“…Beyond affecting constituent channels and junctions, changes in cell membrane configuration with stretch may alter fundamental electrical properties such as capacitance [93]. Although there have been few studies of mechanical effects on myocyte membrane capacitance [106,107], indirect evidence in intact tissue preparations has implicated changes in membrane capacitance in stretch-induced changes in action potential conduction velocity, as described above [49].…”
Section: Cell Scale: Myocyte Electromechanical Couplingmentioning
confidence: 99%
“…buffering (Š imurda et al 2004). It has also been suggested that changes in t-tubule dimensions during mechanical activity accelerate ion exchange by ''assisted convection'' (Kohl et al 2003); this suggestion is supported by the observation that cellular strain reduces the length and volume of the t-tubules, which would be expected to increase fluid exchange between the t-tubule lumen and extracellular space (McNary et al 2011). Such exchange would, therefore, increase with activity, thereby reducing changes in luminal ion concentrations at higher frequencies.…”
Section: The Modelmentioning
confidence: 95%
“…Mechanical stress has a long history of increasing excitability in the heart (mechanoelectric feedback, MEF) (Kohl et al, 2003;Kohl and Sachs, 2002), and initiating arrhythmias (Sachs, 2004b;Baumgarten, 2004). The ventricles of an intact heart can even be be paced with inflation of an intraventricular balloon (Franz et al, 1992).…”
Section: Potential Therapeutic Targets For Gsmtx4 Cardiac Arrhythmiasmentioning
confidence: 99%